Ca2+ Sparks and Ca2+ waves are the subcellular events underlying Ca2+ overload during ischemia and reperfusion in perfused intact hearts - Mattiazzi, Ramona Alicia (2015)
Abnormal intracellular Ca2+ cycling plays a key role in cardiac dysfunction, particularly during the setting of ischemia/reperfusion (I/R). During ischemia, there is an increase in cytosolic and sarcoplasmic reticulum (SR) Ca2+. At the onset of reperfusion, there is a transient and abrupt increase in cytosolic Ca2++, which occurs timely associated with reperfusion arrhythmias. However, little is known about the subcellular dynamics of Ca2+ increase during I/R, and a possible role of the SR as a mechanism underlying this increase has been previously overlooked. The aim of the present work is to test two main hypotheses: (1) An increase diastolic Ca2+ sparks frequency (cspf) constitutes a mayor substrate for the ischemia-induced diastolic Ca2+ increase; (2) an increase in cytosolic Ca2+ pro-arrhythmogenic events (Ca2+ waves), mediates the abrupt diastolic Ca2+ rise at the onset of reperfusion. We used confocal microscopy on mouse intact hearts loaded with Fluo-4. Hearts were submitted to global I/R (12/30min) to assess epicardial Ca2+ sparks in the whole heart. Intact heart sparks were faster than in isolated myocytes whereas cspf was not different. During ischemia, cspf significantly increased relative to preischemia (2.07±0.33 vs. 1.13±0.20 sp/s/100μm, n=29/34, 7 hearts). Reperfusion significantly changed Ca2+ sparks kinetics, by prolonging Ca2+ sparks rise time and decreased cspf. However, it significantly increased Ca2+ wave frequency relative to ischemia (0.71±0.14 vs. 0.38±0.06 w/s/100μm, n=32/33, 7 hearts). The results show for the first time the assessment of intact perfused heart Ca2+ sparks and provides direct evidence of increased Ca2+ sparks in ischemia that transform into Ca2+ waves during reperfusion. These waves may constitute a main trigger for reperfusion arrhythmias.